INVESTIGATING THE CORRELATION BETWEEN CRITICAL THINKING ABILITY AND GRADE ELEVEN STUDENTS’ VOCABULARY ACHIEVEMENT - Hanafi Wibowo (Lingua, 2017)
This research entitled “Investigat ing The Correlation Between CriticalThinking Ability and Grade Eleven Students’ Vocabulary Achievement at SMKBhakti Persada Bekasi” principally aims to investigate whether or not there iscorrelation between critical thinking ability and vocabulary achievement.Thisresearch was conducted on the grade eleven students at SMK Bhakti Persada,PondokGede, Bekasi, at in the Academic year of 2016/2017. Research methodeused in this research was correlation, quantitative and the design was ex-post factodesign.To collect data the researcher used two instruments in the form ofobjective, multiple choice each numbering 30 for X variable and 32 for Y variableout of 50 question items for X and also 50 items for Y having been tried out inclass XI at SMK Bhakti Persada, Pondokgede, Bekasi. The scores obtained fromthe try-out class were used to analyze the validity, reliability, discriminationpower and difficulty index of each question item in two instruments.Thepopulation of this research was grade eleven students consisting of 212 studentsoccupying 7 classes. The number of samples was 37 students seating inaccounting class taken from the population using cluster random technique. Theresults obtained from samples were used to analyze the data using statisticalformulas of Pearson’s Product Moment, preceded by normality and linearity testas the pre-requisite requirements for data analysis.The analysis using SPSS-basedProduct Moment formula produced significance (Sig.) value of 0.000. Since thesignificance value was smaller than (<) Alpha 0.05, Ho is rejected and Ha isaccepted. Accordingly the research concludes that there is significant correlationbetween critical thinking ability and grade eleven students’ vocabularyachievement at SMK Bhakti Persada Bekasi in the Academic Year of 2016/2017.